PELAKSANAAN PENGAWASAN OLEH BADAN MUSYAWARAH (BAMUS) DALAM PENYELENGGARAAN PEMBANGUNAN DI KENAGARIAN BAYUA KECAMATAN TANJUNG RAYA KABUPATEN AGAM - Eviandi Ibrahim; Umul Khair; Asep Ajidin (Ensiklopedia of Journal, 2025)
Abstract: The role of the Nagari Deliberation Board (BAMUS) is highly essential in achieving balanced and equitable development. Therefore, the presence of the Nagari Deliberation Board (BAMUS) within Nagari government, with its various significant functions and authorities, should be able to realize development that aligns with community needs. BAMUS carries out supervision through direct and indirect monitoring. Direct supervision by BAMUS is conducted through Musnag (Nagari Deliberation) and Musrenbang (Planning Deliberation), coordination meetings, direct communication, and field visits. Indirect supervision is carried out through the review of work performance reports (LKPJ), as well as monitoring and evaluation activities.Keywords: Implementation, Supervision, BAMUS, Development, Nagari.